Development of a rotation phantom for phase contrast MRI sequence validation and quality control. Issue 6 (23rd June 2020) - Vali, Alireza; Schmitter, Sebastian; Ma, Liliana; Flassbeck, Sebastian; Schmidt, Simon; Markl, Michael; Schnell, Susanne
Abstract : Purpose: To develop a reliable, consistent, and reproducible reference phantom for error quantification of phase‐contrast MRI so it can be used for validation and quality control. Methods: An air‐driven rotation phantom consisting of a steadily rotating cylinder surrounded by a static ring both filled with agarose gel was developed. Rotational speed was measured and controlled in real time using an optical counter and a closed‐loop controller. Consistency of the phantom was assessed by recording variations in rotational speed. The phantom was imaged with 2D phase‐contrast MRI, and the velocity at each point was compared with analytically predicted velocity. Additionally, to examine reproducibility, the phantom was run with the same rotational speed on 2 different days and imaged using the same phase‐contrast MRI protocol. Results: The rotation phantom provided consistent rotational speed with 2 revolutions per minute SD from the set value for 20 min. Comparison between predicted and measured velocities demonstrated excellent agreement (intraclass correlation coefficient of 0.99). The RMS error in velocity components were less than 1% of maximum value. The scan–rescan experiment showed that the phantom can reproduce the same velocity distributions (intraclass correlation coefficient of 0.99) using the same rotational speed and MRI settings. Conclusion: The developed rotation phantom provided well‐defined and reproducible linear velocity distributions, which can be used for systematic and quantitative error analysis of phase‐contrast MRI for a range of known velocities.